PENILAIAN KUALITAS TANAH PADA BEBERAPA TIPE PENGGUNAAN LAHAN DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Suleman, Salma; Rajamuddin, Ulfiyah A.; Isrun, Isrun (AGROTEKBIS, 2016)
This research aimed to evaluate soil quality criteria in Sigi Biromaru District Sigi Regency based on some types of land use. The research method used was descriptive-explorative method which its variables were conducted through field surveys and supported by soil analysis from laboratory. Results of soil analysis were then assessed its quality by using scoring method at each indicator. Results of this research showed that soil in Sigi Biromaru District Sigi Regency based land use had soil quality criteria ranged from healthy soil to less healthy soil. On mixed farming area had the highest scoring value 2.83 (healthy soil criteria), whilst rice field had scoring value 2.66 (less healthy soil criteria) and on horticulture area had the lowest scoring value 2.5 (less healthy soil criteria).Key Words: Land use, soil quality.